Small-scale vegetable oil extraction - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Small-scale vegetable oil extraction 1995 107pp price UKL 15 00 ISBN 085954 387 0